The Mahā Kumbh Melā in Allahabad 2013 - Gäbel, Cora (Zeitschrift für Religionswissenschaft, 2018)
The following article deals with the Mahā Kumbh Melā1 in Allahabad (Uttar Pradesh, northern India) and the practices of Hindu world renouncers2 during this festival. In 2013, the year under study, approximately 120 million renouncers and lay pilgrims attended the festival. After a brief overview of the academic discussion on Hindu renunciation, the article proceeds to outline the mythology, history, and meaning of the Kumbh Melā. Subsequently, it presents the festival from the renouncers’ point of view. This section of the article summarizes the functions of the festival, describes two particular forms of meals (bhaṇḍārās and annakṣetras), and outlines the daily routine of the participants. Finally, the article discusses the inner-worldly asceticism of lay pilgrims, the main participants, as well as the ritual bathing during the festival, a crucial part of the Kumbh Melā for all participants.